The Effect of Brain Gymnastics on Fine Motor Skills in Children at Al Kautsar Islamic Kindergarten in South Jakarta City in 2024 - Heni Purwanti; Tantri Wenny Sitanggang; Ernawilis; Laila Anjani (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
Fine motor skills are essential in early childhood development, supporting daily activities and school readiness. Brain gymnastics is a series of structured and simple movements involving coordination between the brain and body, designed to stimulate the nervous system and enhance motor development in a playful way. This study used a pre-experimental design with a one-group pretest-posttest approach. A total of 33 children aged 4–6 years were selected using purposive sampling. The Denver Developmental Screening Test (DDST) was used as the main instrument, completed through parent interviews and direct observation by the researcher before and after the brain gymnastics intervention. Data were analyzed using the Wilcoxon Signed-Rank Test. Before the intervention, 21 children (63.3%) showed delayed fine motor development. After the intervention, 30 children (90.9%) reached the normal developmental stage appropriate for their age. The Wilcoxon Signed-Rank Test revealed a significant difference with a p-value of 0.000 (p < 0.05), indicating a statistically significant improvement in fine motor skills. The results demonstrate that brain gymnastics effectively improves fine motor skills in children aged 4–6 years. Through engaging and coordinated movements, brain gymnastics stimulates neural pathways and supports optimal motor development. It can be applied as a fun and practical method of stimulation in early childhood education settings.